Financial Distress Sebagai Mekanisme Mediasi Antara Profitabilitas, Struktur Modal, dan Nilai Perusahaan: Peran Moderasi Komisaris Independen - Henny Wirianata; Viriany Viriany; Sri Sundari; Kartini Kartini (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the influence of profitability and capital structure on firm value, taking into account the role of financial condition as a mediating variable and corporate governance as a moderating variable. The main variables used include profitability (ROA), capital structure (DER), financial condition (Altman Z-score), firm value (Tobin’s Q/PBV), and independent commissioners as a moderating variable. This study employs a quantitative approach using secondary data analyzed via regression models, moderation tests, and the Sobel mediation test. The study was conducted on 45 companies from the property and real estate sectors that met the sample criteria, covering the period from 2019 to 2024. The results indicate that profitability does not significantly affect financial condition or firm value. Conversely, capital structure has a significant negative effect on financial condition but a significant positive effect on firm value. Furthermore, independent commissioners were found to mitigate the negative impact of capital structure on financial health. This study contributes by integrating mediation and moderation roles into a single model, and demonstrates that the relationship between financial variables and firm value is complex and contextual. These findings have implications for management and investors in understanding the importance of managing capital structure and financial health, and reinforce the role of corporate governance in risk management.